Self-Regulating Capacity and Learning Attributions Among Indonesian EFL High School Students - Masitho, Prianka Ratu; Anam, Syafi'ul (Universitas Pendidikan Ganesha, 2025)
Self-regulated learning (SRL) is needed for students to use various learning strategies. As one of instruments in cognitive and behavioural SRL, language learning strategies (LLS) and attributions are deemed to possess commands that enhance second/foreign language (L2) learning processes. However, several issues were highlighted in regards to the LLS taxonomy and its instrumentation, Strategy Inventory for Language Learning (SILL). Due to definitional fuzziness of the LLS taxonomy and inadequacy of psychometric instruments of SILL, this study was carried specifically using the Self-regulating Capacity (SRC) construct. In addition, empirical evidence on links between students’ attributions and SRC to their L2 achievement is still lacking. This study was attempted to examine the association between SRC and learning attributions to English achievement. This research was conducted quantitatively with a cross-sectional design. The SRC Scale and Language Achievement Attribution Scale (LAAS) were administered to 319 Indonesian EFL high school students. Data analyses of participants’ responses on both questionnaires were concluded in the following three major findings. First, descriptive analysis showed that out of SRC categories, Indonesian EFL students employed environmental control with the highest capacity during English learning. Second, in perceiving learning success or failure, Indonesian EFL attributed their English achievement due to internal causes (i.e., ability, effort and mood) rather than to external causes (i.e., task difficulty, teacher, and luck factors). Third, regression analysis revealed that SRC and learning attributions explained 74% variance of English achievement. Further, implications for future research and education practice were provided.